The Relationship of Mother's Knowledge, Attitudes and Actions Regarding Balanced Nutrition and the Incident of Wasting in Toddler - Aulia, Dinda Zalfa; Eliska, Eliska; Suraya, Rani (Indonesian Journal of Global Health Research, 2024)
Wasting is a nutritional status problem where a toddler's weight decreases drastically, or even below the normal range where the toddler's weight does not match his height or z score. Objective: The aim of this research is to determine the relationship between mothers' knowledge, attitudes and actions regarding balanced nutrition with the incidence of wasting in toddlers in Medan Deli District, Medan City. Method: The type of research used is analytical research with a cross sectional approach. The population in this study was 32 mothers who had wasting toddlers. The samples used in the research were mothers who had wasting toddlers aged 24 months - 59 months in the work area of the Medan Deli Health Center, Medan City, totaling 32 respondents using total sampling techniques. Results: The research results that have been collected using questionnaires and data analyzed using univariate and bivariate analysis show that the majority of mothers have sufficient knowledge, 16 respondents (50.0%), 16 respondents (50.0%) have positive and negative attitudes and 27 respondents (84.4%) had good actions. The chi square test shows that there is a relationship between mothers' knowledge about balanced nutrition and the incidence of wasting in toddlers, p = 0.048, there is a relationship between mothers' attitudes about balanced nutrition and the incidence of wasting in toddlers, p = 0.033, and there is a relationship between mothers' attitudes about balanced nutrition and the incidence of wasting. in toddlers p = 0.033. There is a relationship between maternal actions regarding balanced nutrition and the incidence of wasting in toddlers, p = 0.032. Conclusion: There is a significant relationship between mothers' knowledge, attitudes and actions regarding balanced nutrition and the incidence of wasting in toddlers in Medan Deli District, Medan City.